2014
DOI: 10.3389/fonc.2014.00199
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Radioembolization as a Bridge to Liver Surgery

Abstract: Treatment of oncologic disease has improved significantly in the last decades and in the future a vast majority of cancer types will continue to increase worldwide. As a result, many patients are confronted with primary liver cancers or metastatic liver disease. Surgery in liver malignancies has steeply improved and curative resections are applicable in wider settings, leading to a prolonged survival. Simultaneously, radiofrequency ablation (RFA) and liver transplantation (LTx) have been applied more commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…Radioembolization before surgical resection, as in HCC and metastatic colorectal cancer, could be promising in intrahepatic cholangiocarcinoma as well. Downstaging occurs in 10%, and inducing contralateral hypertrophy seems feasible (65,72). In a small cohort combining radioembolization with chemotherapy, downstaging occurred in 22%, significant hypertrophy of the contralateral lobes was seen in all patients, and 18% were radically resected (74).…”
Section: Clinical Outcome and Tumor Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Radioembolization before surgical resection, as in HCC and metastatic colorectal cancer, could be promising in intrahepatic cholangiocarcinoma as well. Downstaging occurs in 10%, and inducing contralateral hypertrophy seems feasible (65,72). In a small cohort combining radioembolization with chemotherapy, downstaging occurred in 22%, significant hypertrophy of the contralateral lobes was seen in all patients, and 18% were radically resected (74).…”
Section: Clinical Outcome and Tumor Responsementioning
confidence: 99%
“…In HCC, the downstaging success rate with radioembolization is around 50% (range, 29%-67%), with a median time to downstaging of 3.1-4 mo (65). In downstaging HCC, radioembolization is a suitable alternative to TACE, but downstaging should not be restricted to HCC alone (65).…”
Section: Clinical Outcome and Tumor Responsementioning
confidence: 99%
“…In addition to salvage therapy and primary treatment of various malignancies for patients who have contraindications to surgery, 90 Y microspheres can be used as an adjunct to surgery (22). 90 Y microsphere therapy is efficacious in downstaging patients with hepatocellular carcinoma, metastatic colorectal cancer, and cholangiocarcinoma, making them more amenable to surgical resection (13,22). Radioembolization can also reduce tumor burden, slow disease progression, and provide a bridge to liver transplantation (22).…”
Section: Indicationsmentioning
confidence: 99%
“…TARE using 90-Y-tagged glass beads has been shown to be safe and probably effective in patients with unresectable HCC [13][14][15]. A recent meta-analysis suggested that TARE is significantly better than TACE in terms of survival, time to progression, hospitalization time, and complication rates for patients with HCC [16]. A further role of TARE in advanced HCC patients is as a conversion treatment for patients considered otherwise unresectable or even as a bridge to transplantation [17].…”
Section: Tace For Hccmentioning
confidence: 99%